Analisis Pengembangan Sintak Model Pembelajaran Project-based Learning pada Mata Pelajaran Dasar Listrik dan Eelektronika di Sekolah Vokasional - Purwanto, Purwanto; Tamrin, Agusti; Suharno, Suharno (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2023)
This study aims to analyze the results of developing project-based learning methods for solving problems. Development is carried out by adding Project Based Learning syntax to the Learning Implementation Plan. This research method uses a Research and Development approach. The steps taken in this study include 1) needs analysis, 2) model development, 3) model validation, 4) limited trials, and 5) extended trials. The population and sample studied were vocational school students, with a total sample of 32 students. Sample selection using simple random sampling (simple random) and purposive random sampling. The analytical tools used are the normality test, homogeneity test and difference test. Based on the analysis results, it is known that the data on learning outcomes before the PjBL action averaged 79.66 with a deviation of 3.2. The lowest score is 77, and the highest score is 89. The average learning outcome data after the PjBL action is 87.58, with a deviation of 4.2. The lowest score is 77, and the highest score is 99. Based on the analysis results, it is known that the average learning outcome data before the PjBL action is 77.19, with a deviation of 1.5. The lowest score is 75, and the highest score is 80. The average learning outcome data after the PjBL action is 82.18, with a deviation of 3.7. The lowest score was 77, and the highest score was 97. The Wilcoxon Test analysis results showed differences in the score before project-based learning and the score after project-based learning. There is an influence of project-based learning on student learning values. Based on the analysis of learning development trials outlined in the lesson plan, project-based learning is feasible to use in improving student learning outcomes.